The Law on Using Pawned Goods Without the Owner's Permission Perspec-tive of Dsn Fatwa Number 25/Dsn-Mui/Iii/2002 Concerning Rahn (Case Study of Sipolu-Polu Village, Panyabungan District, Mandailing Natal Regency) - Siregar, Habibulloh; Zuhri, Ahmad (LEGAL BRIEF, 2024)
Pawning is permitted in Islamic law. In Islam, pawning is a contract that has the principle of mutual assistance that does not seek profit. Pawned goods or also called marhun are collateral or ransom goods to obtain loans. The use of pawned goods that occurred in Sipolu-polu Village is that the pawned goods are used by employees of the recipient of the pawned goods. The occurrence of the use of pawned goods is very interesting to study. Therefore, the purpose of this study is to determine the law on the use of pawned goods by the recipient of the pawned goods in Sipolu-polu Village. This research method uses qualitative with a descriptive approach and to obtain data, the author conducted observations and interviews with the intention of knowing and observing directly about the law on using pawned goods without the owner's permission that occurs in the Sipolu-polu Village community. The results of the study stated that the law on the use of pawned goods without the owner's permission in Sipolu-polu Village is not allowed or haram according to DSN-MUI Fatwa Number 25/III/2002 because the murtahin may not take advantage of the pawned goods without the permission of the rahin. This is based on the fact that in a pawn the principal agreement is a debt, and in a debt, what applies is the principle of mutual assistance (ta'awun) and not seeking profit